Knowledge, attitudes, and practices of Crimean Congo hemorrhagic fever among livestock value chain actors in Kagadi district, Uganda. - Dreck Ayebare; Muzafalu Menya; Alex Mulyowa; Adam Muhwezi; Robert Tweyongyere; Stella A Atim (Public Library of Science (PLoS), 2023)
Background Crimean Congo hemorrhagic fever (CCHF) is a zoonotic tick-borne disease with an increasing number of outbreaks among communities in Uganda. Following the disease outbreak in the western district of Kagadi on 20th February 2020, a KAP survey was conducted to identify knowledge gaps and at-risk behaviors related to the disease among livestock value chain actors. Methods A household survey using a semi-structured questionnaire was conducted in 399 households in the two sub counties of Bwikara and Ruteete, Kagadi district. A focus group discussion with members of the community was conducted as well as key informant interviews with at-risk individuals. Descriptive and inferential analysis was performed using STATA version 13 (Statacorp Texas; USA). Comparative analysis of the data from the two sub counties was also performed using cross tabulations in STATA, between each independent variable and the subcounty variable. The descriptive and comparative statistics used were minimum, mean and maximum values, standard deviations, frequencies, percentages, chi square values and t-statistics. A chi-square test was then employed on each tabulation, to determine whether there was an association between the two categorical variables or not. The test was set at an alpha level of 0.05, and where the p-value was less than or equal to the alpha value, we concluded that the 2 variables were associated. Results Although majority of the respondents believed in the existence of the disease, only 12.8% had knowledge of prevention measures against CCHF. 67.2% of the respondents reported regular interaction with ticks during routine farm operations and they employed tick control measures on their farms. Although the respondents believe the disease is fatal, almost all of them (99%) would welcome a CCHF survivor back into the community. 95.2% of the respondents actively attended to animals but only 25.8% participated in slaughtering animals. Qualitatively, the technical informants had knowledge about CCHF but non technical informants hardly knew about the disease. Limited funding appropriated for local governments, as well as limited engagement in One health activities were some of the barriers highlighted towards the infection prevention and control activities. Most of the focus group discussion participants knew about the disease, but lacked knowledge on its transmission and prevention. Limited access to personal protective equipment and high exposure to tick-prevalent areas when slaughtering and grazing animals respectively, were the major challenges highlighted. Conclusion Knowledge on CCHF among majority of the respondents was poor. There is a need for educational programs to increase awareness of CCHF in communities. This awareness should be done by both the community leaders and technical people to ensure the community receives enough knowledge on how to prevent and control the disease. To ensure effectiveness of these programs a One health approach should be adopted to implement prevention and control strategies.